2010
DOI: 10.1249/mss.0b013e3181b84a85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Marathon Running Performance

Abstract: The concentrations of air pollution present during marathons rarely exceed health-based national standards and levels known to affect lung function in laboratory situations. Regardless, PM(10) was significantly correlated with performance of women marathon runners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 32 publications
2
47
1
Order By: Relevance
“…A limitation in this cross-sectional study is that influences on endurance performance such as physiological (Landman et al, 2012;Saltin et al, 1995;Saunders et al, 2004) and anthropometric characteristics (Knechtle et al, 2008(Knechtle et al, , 2009Knechtleet al, 2010), training variables (Billat et al, 2001;Knechtle, Wirth, et al, 2010), fluid and food intake (Bürge et al, 2011;Cejka, Knechtle, Knechtle, Rüst, & Rosemann, 2012;Fallon, Broad, Thompson, & Reull, 1998;Onywera et al, 2004), medical problems (Scheer & Murray, 2011) and environmental conditions of the race (El Helou et al, 2012;Ely, Cheuvront, Roberts, & Montain, 2007;Marr & Ely, 2010;Vihma, 2010) were not taken into consideration. However, this study reveals valuable data, because it provides insight into the development of participation and performance in 100-km ultramarathon worldwide.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…A limitation in this cross-sectional study is that influences on endurance performance such as physiological (Landman et al, 2012;Saltin et al, 1995;Saunders et al, 2004) and anthropometric characteristics (Knechtle et al, 2008(Knechtle et al, , 2009Knechtleet al, 2010), training variables (Billat et al, 2001;Knechtle, Wirth, et al, 2010), fluid and food intake (Bürge et al, 2011;Cejka, Knechtle, Knechtle, Rüst, & Rosemann, 2012;Fallon, Broad, Thompson, & Reull, 1998;Onywera et al, 2004), medical problems (Scheer & Murray, 2011) and environmental conditions of the race (El Helou et al, 2012;Ely, Cheuvront, Roberts, & Montain, 2007;Marr & Ely, 2010;Vihma, 2010) were not taken into consideration. However, this study reveals valuable data, because it provides insight into the development of participation and performance in 100-km ultramarathon worldwide.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…Surprisingly, in a world which so highly covets athletic competition and where seconds may mark the difference between first place, fifth place, or even a world record, a dearth of literature exists examining the effects of PM inhalation on exercise performance. A recent publication, examined the times of the top three finishers in seven US marathons over the course of 8-28 years and identified performance decrements associated with PM 10 (< 10 µm) among women but not men (Marr & Ely, 2010). earlier investigated the effects of PM 1 inhalation on male subjects who completed two, 6 min work accumulation rides in low PM (LPM) separated by 48 h and followed by two, 6 min work accumulation rides in high PM (HPM) seven days later under laboratory conditions where fresh particulate matter was generated from a 2-cycle engine.…”
Section: Research Articlementioning
confidence: 99%
“…General recommendations for preparing to train and compete in these environments are provided in Table 35.5. by laboratory-based research, although a fi eldbased retrospective analysis showed that "acceptable" levels (i.e., not "unhealthy" levels) of PM were negatively correlated to marathon performance in female recreational runners (Marr & Ely, 2010).…”
Section: Discussionmentioning
confidence: 96%